Current scenario of organ donation and transplantation in Kerala, India - Mekkodathil, Ahammed; Asim, Mohammad; Sathian, Brijesh; Rajesh, Elayedath; Kumar, Rajeev; Simkhada, Padam; van Teijlingen, Edwin (Nepal Journal of Epidemiology, 2019)
Organ donation rate in India is very low when compared to many developed countries which contribute to the deaths due to organ failures every year. Kerala, one of the southern states in India with best health statistics in the country, has a deceased organ donation programme and has an organ donation rate higher than national average. However, there is a significant decline in number of donations in recent years.